2021
DOI: 10.3390/f12121674
|View full text |Cite
|
Sign up to set email alerts
|

Does Mixing Tree Species Affect Water Storage Capacity of the Forest Floor? Laboratory Test of Pine-Oak and Fir-Beech Litter Layers

Abstract: During the last decade, tree species mixing has been widely supported as a silvicultural approach to reduce drought stress. However, little is known on the influence of tree species mixing on physical properties and the water storage capacity of forest soils (including the forest floor). Thus, the study aimed to analyze the effect of mixing pine needles and oak leaves and mixing fir needles and beech leaves on hydro-physical properties of the litter layer during laboratory tests. We used fir-beech and pine-oak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Similarly, several previous studies have also found that broadleaf litter had a larger storage capacity compared to needle litter. Walsh and Voigt (1977), Sato et al (2004) Li et al (2013 and Ilek et al (2021) found that the storage capacity per unit dry weight of broadleaf litter was higher than that of needle litter by factors of up to 1.6, 1.8, 2.65 and 1.4 respectively. In general, the larger storage capacity in broadleaf litter compared to needle litter can be related to structural differences between the two litter types (Klamerus-Iwan et al, 2020;Li et al, 2013).…”
Section: The Storage and Retention Capacity Of Forestfloor Broadleaf ...mentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, several previous studies have also found that broadleaf litter had a larger storage capacity compared to needle litter. Walsh and Voigt (1977), Sato et al (2004) Li et al (2013 and Ilek et al (2021) found that the storage capacity per unit dry weight of broadleaf litter was higher than that of needle litter by factors of up to 1.6, 1.8, 2.65 and 1.4 respectively. In general, the larger storage capacity in broadleaf litter compared to needle litter can be related to structural differences between the two litter types (Klamerus-Iwan et al, 2020;Li et al, 2013).…”
Section: The Storage and Retention Capacity Of Forestfloor Broadleaf ...mentioning
confidence: 98%
“…Laboratory experiments on forest litter samples have been conducted to quantify their water storage properties (e.g. Guevara‐Escobar et al, 2007; Ilek et al, 2021; Li et al, 2013; Putuhena & Cordery, 1996; Sato et al, 2004; Walsh & Voigt, 1977). Fewer studies (to our knowledge) have measured the water retention capacity of litter in situ (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, several previous studies have also found that broadleaf litter had a larger storage capacity compared to needle litter. Walsh & Voigt (1977), Sato et al, (2004) Li et al (2013), and Ilek et al (2021) found that the storage-capacity per unit dry weight of broadleaf litter was higher than that of needle litter by factors of up to 1.6, 1.8, 2.65, and 1.4 respectively. In general, the larger storage capacity in broadleaf litter compared to needle litter can be related to structural differences between the two litter types (Klamerus-Iwan et al, 2020;Li et al, 2013).…”
Section: The Storage and Retention Capacity Of Forest-floor Broadleaf...mentioning
confidence: 99%
“…Whereas canopy interception losses have been characterized across numerous forest sites (Yue et al, 2021), only a few previous studies have evaluated the storage and retention capacity of the forest-floor litter layer, and most of these studies have been focused on the leaf component (e.g., Gerrits and Savenije, 2011;Klamerus-Iwan et al, 2020). Laboratory experiments on forest litter samples have been conducted to quantify their water storage properties (e.g., Walsh and Voigt, 1977;Putuhena and Cordery, 1996;Sato et al, 2004;Guevara-Escobar et al, 2007;Li et al, 2013;Ilek et al, 2021). Fewer studies (to our knowledge) have measured the water retention capacity of litter in situ (e.g., Brechtel, 1969;Thamm and Widmoser, 1995;Schaap and Bouten, 1997;Gerrits et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas canopy interception losses have been characterized across numerous forest sites (Yue et al, 2021), only a few previous studies have evaluated the storage and retention capacity of the forest-floor litter layer, and most of these studies have been focused on the leaf component (e.g., Gerrits and Savenije, 2011;Klamerus-Iwan et al, 2020). Laboratory experiments on forest litter samples have been conducted to quantify their water storage properties (e.g., Walsh and Voigt, 1977;Putuhena and Cordery, 1996;Sato et al, 2004;Guevara-Escobar et al, 2007;Li et al, 2013;Ilek et al, 2021). Fewer studies (to our knowledge) have measured the water retention capacity of litter in situ (e.g., Brechtel, 1969;Thamm and Widmoser, 1995;Schaap and Bouten, 1997;Gerrits et al, 2007).…”
Section: Introductionmentioning
confidence: 99%